Microscopic description of the foliar morphology of Neltuma chilensis (Molina) C.E. Hughes &G.P. Lewis (Bioagro, 2026)
Neltuma chilensis, a native tree of Central Chile, is historically valued for its ecological and cultural importance, as well as for its resilience to drought. This study aims to characterize the microscopic foliar morphology of this species using histological techniques. Leaves were collected in the Region of Valparaíso, Chile, processed, and analyzed using various staining techniques, examining histological structures and staining affinity. A uniseriate epidermis with non-glandular, conical trichomes and stomata on the adaxial surface was observed; a dorsiventral mesophyll with palisade and spongy parenchyma; and a midrib containing lignified sclerenchyma, phloem, and xylem with tracheids. Dense, granular idioblasts containing mucilage were also identified, likely involved in water retention. These findings provide information on the anatomical structures associated with the adaptation of N. chilensis to extreme abiotic conditions, such as drought and climates with high fluctuations between maximum and minimum temperatures.
Keywords: Foliar anatomy; histological description; histological techniques; morphology